Production of chitosan based films enriched with oregano essential oil for increased antibacterial activity - Fernandes, I.P. (2014)
During the last years, there has been an increasing interest in developing bio-based active films to improve food safety, extend food shelf life and reduce the use of chemical preservatives. Chitosan, a deacetylated derivative of chitin, is a linear polysaccharide consisting of -(1 4) glucosamine and N-acetylglucosamine residues with potential to be used as a food packaging/coating material. This biopolymer can be used in a wide range of applications in the food industry due to several interesting properties such as its biodegradability, biocompatibility, non-toxicity, antimicrobial activity and versatile physical properties such as its film-forming capacity. Recently, different strategies have been explored to improve its natural properties for the development of food packaging/coating materials with enhanced antimicrobial activity. In particular, the incorporation in chitosan films of essential oils (EO) with acknowledged antibacterial properties, as an alternative of synthetic preservatives, is a matter of great interest since they are generally perceived by consumers as being “natural” food additives. Thus, the objective of this work was the production of chitosan films enriched with oregano EO to further improve the natural antimicrobial properties of chitosan. The obtained films which were then evaluated for its antibacterial activity.